Indacaterol, glycopyrronium, and mometasone: Pharmacological interaction and anti-inflammatory profile in hyperresponsive airways. (October 2021) - Rogliani, Paola; Ritondo, Beatrice Ludovica; Facciolo, Francesco; Matera, Maria Gabriella; Nikolaev, Ivan; Calzetta, Luigino
Abstract: LABA/ICS and LABA/LAMA/ICS combinations elicit beneficial effects in asthma. Specific evidence concerning the impact of combining indacaterol acetate (IND), glycopyrronium bromide (GLY), and mometasone furoate (MF) on human airway hyperresponsiveness (AHR) and airway inflammation is still missing. The aim of this study was to characterize the synergy of IND/MF and IND/GLY/MF combinations, both once-daily treatments for asthma, in hyperresponsive airways. Passively sensitized human medium and small airways were stimulated by histamine and treated with IND/MF (molar ratio: 100/45, 100/90) and IND/GLY/MF (molar ratio: 100/37/45, 100/37/90). The effect on contractility and airway inflammation was tested. Drug interaction was assessed by Bliss Independence equation and Unified Theory. IND/MF 100/90 elicited middle-to-very strong synergistic relaxation in medium and small airways (+≈20–30% vs. additive effect, P < 0.05), for IND/MF 100/45 the synergy was middle-to-very strong in small airways (+≈20% vs. additive effect, P < 0.05), and additive in medium bronchi (P > 0.05 vs. additive effect). IND/GLY/MF 100/37/45 and 100/37/90 induced very strong synergistic relaxation in medium and small airways (+≈30–50% vs. additive effect, P < 0.05). Synergy was related with significant (P < 0.05) reduction in IL-4, IL-5, IL-6, IL-9, IL-13, TNF-α, TSLP, NKA, SP, and non-neuronal ACh, and enhancement in cAMP. IND/MF and IND/GLY/MF combinations synergistically interact in hyperresponsive medium and small airways and modulate the levels of cytokines, neurokinins, ACh, and intracellular cAMP. The concentrations of MF in the combinations modulate the effects in the target tissue. Graphical Abstract: ga1